Preparing Postgraduates for the Profession: Toward Translingual Pedagogical Practices in Advanced Graduate Student Writing Instruction in Germany - Edlich, Micha Gerrit Philipp (Journal of Academic Writing, 2020)
Contributing to the literature on translingual pedagogies outside the US or Canada, this article discusses the design of a hybrid instructional format for advanced multilingual doctoral students and post-doctoral researchers offered by a bilingual writing center at a mid-sized university in Germany. Meant to prepare participants for future careers in academia and professional demands in different national, cultural, and linguistic environments, this format provides the opportunity to explore academic genres that tend to receive less attention in graduate education than journal articles, book chapters, or genres needed to complete degree requirements. By the end of the course, participants will have a submission-ready portfolio including an academic CV, a job letter, a (sample) letter of recommendation, and teaching and diversity statements. To achieve these specific outcomes and to develop the advanced professional academic writing competencies needed in multicultural and multilingual contexts, participants will have to draw on their diverse linguistic backgrounds and prior experiences in these kinds of settings. Informed also by other recent theoretical and empirical work on translingualism and translingual pedagogies in global contexts, this format adopts the use of translation proposed by Horner (2017) to move beyond the monolingual and, to a lesser extent, multilingual paradigms. While it has yet to be tested empirically, the design represents an alternative to more traditional (and usually monolingual) modes of instruction. This article concludes by discussing limitations and implications of the approach to translingual pedagogies taken here.